Structure, morphology and hydrogen storage properties of a Ti0.97Zr0.019V0.439Fe0.097Cr0.045Al0.026Mn1.5 alloy - Murshidi, Julie; Paskevicius, Mark; Sheppard, Drew; Buckley, Craig (Elsevier Ltd, 2011)
The Ti0.97Zr0.019V0.439Fe0.097Cr0.045Al0.026Mn1.5 alloy is a hexagonal C14 Laves phase material that reversibly stores hydrogen under ambient temperatures. Structural changes are studied by XRD and SEM with regard to hydrogenation and dehydrogenation cycling at 25, 40 and 60 °C. The average particle size is reduced after hydrogenation and dehydrogenation cycling through decrepitation. The maximum hydrogen capacity at 25 °C is 1.71 ± 0.01 wt. % under 78 bar H2, however the hydrogen sorption capacity decreases and the plateau pressure increases at higher temperatures. The enthalpy (ΔH) and entropy (ΔS) of hydrogen absorption and desorption have been calculated from a van’t Hoff plot as −21.7 ± 0.1 kJ/mol H2 and −99.8 ± 0.2 J/mol H2/K for absorption and 25.4 ± 0.1 kJ/mol H2 and 108.5 ± 0.2 J/mol H2/K for desorption, indicating the presence of a significant hysteresis effect.